Photosynthetic Physiological Characteristics of Water and Nitrogen Coupling for Enhanced High-Density Tolerance and Increased Yield of Maize in Arid Irrigation Regions - Guo, Yao; Yin, Wen; Fan, Hong; Fan, Zhilong; Hu, Falong; Yu, Aizhong; Zhao, Cai; Chai, Qiang; Aziiba, Emmanuel Asibi; Zhang, Xijun (Frontiers in Plant Science, 2021)
To some extent, the photosynthetic traits of developing leaves of maize are regulated systemically by water and nitrogen. Yet it remains unclear whether photosynthesis is systematically regulated via water and nitrogen when the maize crops grown under close (high density) planting conditions. To address this, a field experiment was designed that had a split-split plot arrangement of treatments. Two irrigation levels on local traditional irrigation level (high, I2, 4050 m3 ha-1) and it reduced by 20% (low, I1, 3240 m3 ha-1) formed the main plots; two levels of nitrogen fertilizer on local traditional nitrogen level (high, N2, 360 kg ha-1) and it reduced by 25% (low, N1, 270 kg ha-1) formed the split plots; three planting densities of low (D1, 7.5 plants m-2), medium (D2, 9.75 plants m-2), and high (D3, 12 plants m-2) formed the split-split plots. The grain yield, gas exchange, and chlorophyll a fluorescence of the closely planted maize were assessed. The results showed that water–nitrogen coupling regulated their net photosynthetic rate (Pn), stomatal conductance (Gs), transpiration rate (Tr), quantum yield of non-regulated non-photochemical energy loss [Y(NO)], actual photochemical efficiency of PSII [Y(II)], and quantum yield of regulated non-photochemical energy loss [Y(NPQ)]. When maize plants were grown at low irrigation with traditional nitrogen and at a medium density (i.e., I1N2D2) they had higher Pn, Gs, and Tr than those grown under traditional treatment (i.e., I2N2D1). Moreover, the increased photosynthesis in leaves of maize in the I1N2D2 treatment was mainly caused by decreased Y(NO), and increased Y(II) and Y(NPQ). The coupling of 20%-reduced irrigation with the traditional nitrogen application boosted the grain yield of medium density-planted maize, whose Pn, Gs, Tr, Y(II), and Y(NPQ) were enhanced and its Y(NO) reduced. Redundancy analysis revealed that both Y(II) and SPAD were the most important physiological factors affecting maize yield performance, followed by Y(NPQ) and NPQ. Using the 20% reduction in irrigation and traditional nitrogen application at a medium density of planting (I1N2D2) could thus be considered as feasible management practices, which could provide technical guidance for further exploring high yields of closely planted maize plants in arid irrigation regions.